(untitled) (World Bulletin of Management and Law, 2022)
In this article, the author studied the actions of our country and advanced foreign countries to ensure the participation of members of the public in the criminal process, to widely use their assistance in solving crimes. The opinions of scientists on ensuring the safety of members of the public participating in the criminal process are also considered. Based on the above analysis, the author presents a number of proposals and recommendations on legislation and law enforcement